Measuring Physical Activity Levels of Undergraduate Sport Sciences’ Students Using Self-Report Questionnaires and Accelerometers - Krommidas, Χαράλαμπος; Georgiou, Αθανάσιος; Galanis, Ευάγγελος; Vlahos, Όμηρος; Tzioumakis, Γιάννης; Digelidis, Νικόλαος; Papaioannou, Αθανάσιος (Inquiries in Physical Education and Sport, 2021)
The purpose of the present manuscript was to record physical activity (PA) levels of undergraduate sport science students using self-report questionnaires and motion sensors (accelerometers). For this purpose, two studies were performed. Participants in the first study were 102 male and 91 female students (N = 193), aged 18 to 24 years (Mage: 20.49 ± 1.31 years), who completed two valid and reliable questionnaires measuring their PA and reported their weight and height. The second study involved 21 male and 16 female students (N = 37), aged 19 to 22 years (Mage: 20.19 ± .97 years), who wore an accelerometer device for seven consecutive days (GT3X+ Acti-graph). In addition, weight and height were measured with a portable medical scale and a stadiometer. The results from the self-report questionnaires (1st study) showed that the vast majority of the undergraduate students (88.2%) were sufficiently physically active performing more than 60 minutes of moderate to vigorous PA (MVPA) daily. Significant differences also were found in PA between the years of study, while no statistically significant differences were found between male and female students. Regarding the results from the accelerometers (2nd study), it was shown that the vast majority of the undergraduate students (67.6%) performed more than 10.000 steps per day, while 83.8% performed more than 30 minutes of MVPA daily. Finally, the vast majority of students showed a normal Body Mass Index (BMI) in both studies. The above results are very optimistic regarding the PA levels of young adults.